Interaction of Nature and Culture - Gendrolis, Edmundas (Problemos, 1991)
Some economical-cultural types of the possessive and productive economy and their influence upon environment are considered in the paper. Based upon the analysis of the hypotheses of H. Child, P. Bradewood, and L. Binford the ecological, demographical, and productive premises of the productive economy are discussed. Numerous examples of extensive development of stock-breeding demonstrate the degrading impact upon environment and culture. The theories of culture which do not take into account the influence of ecological factors, is said, to be one-sided. The general methodological principles of the analysis of culture is said to attain scientific value only when the interaction of culture and nature is taken into account.